Weighing on languages: Indonesian parents' perspectives on bilingualism - Arapa Efendi (Universitas Katolik Indonesia Atma Jaya, 2020)
The paper focuses on the micro-level language policy where parents are the primary ‘actors’ to socialize language(s) to their children in the family circle. This small-scale study aims to find out 1) parent’s language attitudes towards bilingualism; 2) how the attitudes contribute to the decision making on language policy in the family; 3) and what efforts or strategies for maintaining the heritage language (HL). Data were collected from questionnaires to 28 Indonesian parents (from diverse ethnic backgrounds). To gain deeper insights, interviews were also conducted to investigate individual perceptions, feelings, and experience over bilingualism. Based on the analysis, it is found that although most of the families are bilingual with 3-4 languages being spoken at home, there is a limited context where interaction is carried out in HLs. The majority of respondents reported that it is only used to close relatives. The maintenance of HL is symbolic rather than strategic; it is perceived as important because of the sense of family hood to the language. This is confirmed in the following finding that parents feel that national language is far more important (65%) than the heritage language (34.6%) which is slightly below parents' aspiration for the children to learn a foreign language (38.5%). Also, there is little evidence showing parents’ explicit language policy which may be affected by familiarity and the status of the language, social institutions, community relations, and family structure.